Threads of Creation: Interrogating the Dialectics of Religion, Female Sexuality, and Motherhood in Mahabharata - Sreya Mukherjee (PostScriptum: An Interdisciplinary Journal of Literary Studies)
Mahabharata incorporates themes of political struggle, court intrigues, social hierarchization, cultural clashes, Brahmanical myth-making, sexual tensions and so on. However, one distinctive characteristic of Mahabharata is that theological and metaphysical discourses constitute the strongest undercurrent that not only runs throughout the text but also heavily influences the myriad themes and narratological concerns of the text. Since no critique of motherhood in Mahabharata could be premised outside the theological and metaphysical framework of dharma and adharma i.e., righteousness and unrighteousness, it is therefore imperative to begin the discussion with a comprehensive account of the religious discourse that scaffolds the entire corpus of Mahabharata. Since the theological discourse of dharma and adharma extends strong influence on the treatment of female sexuality and motherhood within Mahabharata, this paper aims to present a dialectical analysis of religion, female sexuality and motherhood through a critical interpretation of the narrative and didactic sections of the Mahabharata. The paper also analyses the narratives surrounding parturition, fertility, and the maternal obligations, highlighting the conflicts and negotiations the women characters within the narratological schema of Mahabharata face in balancing their roles as mothers and their adherence to metaphysical norms. By employing a dialectical lens, this paper seeks to unravel the tensions, contradictions, subversion and negotiations that emerge when theological concerns, female sexuality, and motherhood intersect within the Mahabharata corpus. The paper therefore aims to contribute to the broader discourse on religion and gender by shedding light on the ways in which theological norms and metaphysical themes influenced and in turn were influenced by women’s experiences of sexuality and motherhood.